Projections of land use/cover change and habitat quality in the model area of Yellow River delta by coupling land subsidence and sea level rise - Zhixiong Tang; Rongrong Ning; De Wang; Xinpeng Tian; Xiaoli Bi; Jicai Ning; Zixiang Zhou; Fubin Luo (Ecological Indicators, 2024)
Accurately assessing future land use/cover change (LUCC) and habitat quality (HQ) is vital for ensuring sustainable use of coastal ecosystem services, but most studies ignore the effects of seawater inundation. This study developed a framework based on the PLUS model and InVEST-HQ model that considers seawater inundation due to sea level rise (SLR) and land subsidence. We used this framework to simulate future LUCC and HQ under different scenarios in the Yellow River Delta (YRD). The results showed: (1) From 1991 to 2020, natural wetlands decreased by 39.87 %, non-wetlands decreased by 3.06 %, and artificial wetlands increased by 730.71 %. The overall HQ showed a decreasing trend, with the largest decrease in non-wetlands. (2) Land subsidence occurred in 93.26 % of the YRD, with a subsidence rate of −36.55 mm/year. Underground brine mining is the most important driving factor. About 6.81 %∼11.16 % of the area will be inundated in 2035, and about 9.39 %∼19.27 % of the area will be inundated in 2050. (3) Future multi-scenario simulations show that the Ecological-Protection scenario can minimize the ecological losses caused by seawater inundation. The simulation of future HQ will be underestimated when seawater inundation is not considered. Our study shows that seawater inundation caused by land subsidence and SLR must be taken into account when simulating LUCC and HQ in coastal areas.